DEVELOPMENT OF ECO-FRIENDLY MORTAR UTILIZING INDUSTRIAL WASTE - M Afif Shulhan; Zainul Faizien Haza; Maris Setyo Nugroho (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2022)
Introducing alternatives material on cement-based material manufacturing is the need for environmental sustainability due to the excessive mining of sand from quarry and river bed. At the same time, industrialization headed to an uncontrollable growth of waste. This fact encourages the researcher to enhance the utilization of recycled waste in construction practice. On one side, it affords a solution for waste management, and on the other hand, it contributes to an eco-friendly construction material that minimizes the environmental impact. This paper aims to investigate the usability of the iron waste obtained from the wrought iron industry, as natural fine aggregates replacement. In particular, it focused on studying the physical characteristic of waste aggregates and the effect of partial replacement of natural sand on mortar strength. Mortar cube specimen made with various levels of replacement (0%, 10%, 20% and 30 %) and also various cement-aggregates volumetric proportion, which are 1:3, 1:4, 1:5, 1:6, and 1:7. All of the measurement parameters are taken consecutively based on ASTM norms. The current work remarks that both waste aggregates and natural aggregates reveal complete fulfillment in the aggregate requirement of ASTM standard. Furthermore, the mortar cube test confirmed that the mortar passes the strength grade for N class and O class, which suitable for the above-grade and non-load bearing application.